2004
DOI: 10.1016/s0740-0020(03)00057-1
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of Listeria monocytogenes in different food products commercialized in Portugal

Abstract: Several types of food products on sale in Portugal, were examined for the presence of Listeria monocytogenes. Secondary enrichments, in Fraser broth, were analysed by the mini-Vidas LMO, enzyme-linked fluorescent immunoassay technique. Positive samples were confirmed by isolation on Oxford and PALCAM selective agars followed by biochemical characterization. Of 1035 samples, 72 (7.0%) were positive for L. monocytogenes, the majority being from raw products (milk, meat, fish, flour) although some heat-processed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
56
2
9

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 131 publications
(72 citation statements)
references
References 16 publications
(14 reference statements)
5
56
2
9
Order By: Relevance
“…Segundo esses autores, a detecção desta bactéria em carnes era esperada devido à sua ampla disseminação na natureza, e também sugere que essa bactéria esteve sempre presente nos produtos cárneos e seus derivados, fato que a fez ser considerada como indicadora biológica de contaminação ambiental ou fecal. MENA et al (2004) relatam que, de 17 amostras de carne crua analisadas em Portugal, três (17,7%) estavam contaminadas com L. monocytogenes, afi rmando ainda que a ocorrência dessa bactéria em carnes cruas se deve ao fato de sua natureza ubiquitária.…”
Section: Resultsunclassified
“…Segundo esses autores, a detecção desta bactéria em carnes era esperada devido à sua ampla disseminação na natureza, e também sugere que essa bactéria esteve sempre presente nos produtos cárneos e seus derivados, fato que a fez ser considerada como indicadora biológica de contaminação ambiental ou fecal. MENA et al (2004) relatam que, de 17 amostras de carne crua analisadas em Portugal, três (17,7%) estavam contaminadas com L. monocytogenes, afi rmando ainda que a ocorrência dessa bactéria em carnes cruas se deve ao fato de sua natureza ubiquitária.…”
Section: Resultsunclassified
“…On the other hand, Mena et al [25] reported the prevalence rate of L. monocytogenes was 3.7% in 27 Spanish fermented sausages while Ciftcioglu and Ugur [26] detected only 2.0% in their Turkish samples. The findings of this study showed similarity with the mentioned results.…”
Section: Büyükünal şAkar Turhan Sandikçi Altunatmaz Yilmaz Aksu Ymentioning
confidence: 94%
“…However, due to the fact that the high level of mean occurrence of 50% (CI: 14.8-85.1%; Fig. 2) has been obtained from only two available primary studies (Antunes et al, 2002;Mena et al, 2004), at present the main recommendation can be for enabling actions to address the data gap. Djeniyi, Wegener, Jensen, and Bisgaard (1996) indicated that because L. monocytogenes is not frequently isolated from chickens, it is likely that the live animals may only contribute little to the total contamination of the abattoir, and that the pathogen may be introduced from dirty transport crates.…”
Section: Tablementioning
confidence: 99%
“…The meta-analysis models for fresh meats were based on 16 primary studies (Antunes, Reu, Sousa, Pestana, & Peixe, 2002;Baptista, 2010;Borges, 2009;EFSA, 2005EFSA, , 2006EFSA, , 2007EFSA, , 2009EFSA, , 2010aEFSA, , 2010bEFSA, , 2011bEFSA, , 2012EFSA, , 2013Esteves, Aymerich, et al, 2006;Esteves, Saraiva, Fontes, & Martins, 2006;Mena et al, 2004;Mena, Rodrigues, Silva, Gibbs, & Teixeira, 2008), while the ones for meat products were based on 7 primary studies Esteves, Aymerich, et al, 2006;Esteves, Patarata, Saraiva, & Martins, 2008;Esteves, Saraiva, et al, 2006;Ferreira, Fraqueza, & Barreto, 2007;Mena et al, 2004;Mendes, 2013;Vaz-Velho, Almeida, Mena, Carneiro, & Freitas, 1998). From each of the primary studies (j), the number of samples (s) experiencing the event of interest (i.e., testing positive for a pathogen) and the total number of samples (n) were extracted.…”
Section: Description Of Data Setsmentioning
confidence: 99%